Colorful Collar-Covers and Bells Reduce Wildlife Predation by Domestic Cats in a Continental European Setting - Geiger, Madeleine; Kistler, Claudia; Mattmann, Prisca; Jenni, Lukas; Hegglin, Daniel; Bontadina, Fabio (Frontiers in Ecology and Evolution, 2022)
In many areas, domestic cats are the most abundant predators of small vertebrates. Due to the potential impact on prey populations by cats, there are calls to investigate the effectiveness of visual and acoustic cues as measures to reduce the cat’s hunting efficiency. In this study, we complement previous studies on the efficacy of Birdsbesafe collar-covers (BBScc) in a so far not investigated Continental European setting and explore the effectiveness in combination with a bell. We also evaluate the tolerability of these devices by the cat and the acceptance by their owners. With a randomized and comparative citizen science-based approach we collected data from 26 households with 31 study cats, which were wearing either a BBScc or both a BBScc and a bell. The BBScc reduced the number of birds and ‘reptiles’ brought home by 37% (probability of reduction of 88%). The number of mammals brought home was reduced by 54 – 62%, but only with the additional bell (probability of reduction of >99%). About 25% of the birds that could be dissected were found to have collided with a hard object prior to having been brought home by the cats. Our results are in line with previous findings from Australia, the USA and the UK and highlight the great potential of visual and acoustic cues in reducing hunting success in domestic cats also in Continental Europe. On the other hand, our result show that the number of prey brought home by cats overestimates their hunting bag, if scavenging is not considered. The majority of cat owners reported that their cats habituated quickly to the BBScc. However, frequent scratching in some cats indicates that some individuals may not habituate. Most participating cat owners had a positive attitude towards the BBScc and said that they were willing to use it after the study. However, cat owners reported that their social environment (e.g., neighbors, family, friends) was relatively skeptical, which indicates a need for communication.. To conclude, commercially available devices with visual and acoustic stimuli are straightforward and effective ways to mitigate the potentially harmful effect of domestic cats on wildlife.